IMPROVEMENT OF METHODOLOGY ACCOUNTING MANUFACTURING STOCKS OF ENTERPRISE: PROBLEMS AND AREAS OF SETTLEMENT - O. A. Odnoshevnaya (Фінансово-кредитна діяльність: проблеми теорії та практики)
To date, special attention needs to pay process optimization of accounting manufacturing stocks enterprise, because they serve by the main resource and precondition of each production cycle of enterprise. The article deals with the theoretical and practical problems accounting of manufacturing stocks. Found that needs improving existing classification of reserves through continued expansion of the list of nomenclature. This is due to the expansion of production, a significant proportion of material costs in production costs and rising prices for resources. In the transition to a market economy is important to improve quality indicators of manufacturing stocks. Also content of the article highlights the practical aspects of the turnover, business continuity and rhythm of a single enterprise. By improving the process accounting of manufacturing stocks was developed algorithm optimization of inventory accounting. Also was proposed economic mechanism of improvement of inventory accounting. We believe that the presented recommendations will help resolve current problems in accounting for inventories and improve their records.